Store brand adoption and penetration explained by trust - Paraskevi P. Sarantidou (Spanish Journal of Marketing-ESIC, 2018)
Purpose - This paper aims to explain variations in store brand penetration using trust. It aims to help both retailers and manufacturers predict store brand purchases through an improved understanding of the impact of trust in store brands across 10 different store brand product categories and among nine different grocery retailers. Design/methodology/approach - Data were collected through a telephone survey of 904 participants responsible for the household grocery shopping with a quota of 100 respondents from each of the nine leading grocery retailers in Greece. Findings - The findings provide empirical support that store brand purchases are positively influenced by the consumers’ perceived level of trust toward the retailer’s store brands. Results also confirmed variations in store brand penetration across the ten product categories that were tested, variations among the retailers and variations in the level of trust. Originality/value - This paper is adding to the store brand literature from a quantitative perspective and is contributing to the theory, as there is no clear theoretical view on the effect of trust on store brand purchases.